Product life cycle value as a criterion for evaluating tender offers - N.A. (Економіка, управління та адміністрування)
The need to calculate the value of the life cycle of goods for the evaluation of tender proposals is a topical issue of procurement practice today. The aim of the study is to analyze the content of this evaluation criterion and its impact on public procurement in terms of their transformation into a more transparent and cost-effective process. The author states that this issue in the field of procurement is still insufficiently studied by the Ukrainian scientific community, and therefore there is an objective need to consider the peculiarities of the value of the life cycle of goods. It is noted that the value of a product and its operating costs are the essence of the life cycle cost, at which tenders are evaluated not only by price but also taking into account environmental friendliness, social necessity of product procurement. The key factor in the implementation of this criterion is the need to optimize costs by customers and, accordingly, to improve procurement practices. The issue of determining the value of the product life cycle is also studied, as the Approximate method of its calculation needs to be specified, and customers still avoid the application of this criterion, which negatively affects the transparency and economic feasibility of domestic procurement. At the same time, the author analyzes the state of application of the value of the life cycle of goods by customers in 2021–2022 and finds that there are some positive changes in this area, because customers are beginning to be interested in calculating this parameter. In the future it is necessary to continue tte study of the features of non-price evaluation criteria, so it seems promising to develop a mechanism for calculating the value of the life cycle of the product.